Checkpoints in TNF-Induced Cell Death: Implications in Inflammation and Cancer. Issue 1 (January 2018) - Annibaldi, Alessandro; Meier, Pascal
Abstract : Tumor necrosis factor (TNF) is a proinflammatory cytokine that coordinates tissue homeostasis by regulating cytokine production, cell survival, and cell death. However, how life and death decisions are made in response to TNF is poorly understood. Many inflammatory pathologies are now recognized to be driven by aberrant TNF-induced cell death, which, in most circumstances, depends on the kinase Receptor-interacting serine/threonine-protein kinase 1 (RIPK1). Recent advances have identified ubiquitin (Ub)-mediated phosphorylation of RIPK1 as belonging to crucial checkpoints for cell fate in inflammation and infection. A better understanding of these checkpoints might lead to new approaches for the treatment of chronic inflammatory diseases fueled by aberrant RIPK1-induced cell death, and/or reveal novel strategies for anticancer immunotherapies, harnessing the ability of RIPK1 to trigger immunogenic cell death. Trends: Although long recognized as a component of inflamed tissues, the potential role of cell death as an active component contributing to tissue homeostasis, inflammation, and disease pathogenesis has only recently gained attention. TNF is a pleiotropic cytokine with key roles in inflammation, triggering either NF-κB activation or RIPK1 kinase-dependent cell death. Suppression of TNF-induced cell death is an active process controlled at multiple levels by diverse checkpoints, operating at both transcriptional and post-translational levels. Signaling pathways of Ub-dependent phosphorylation of RIPK1 by IKK2 and MK2 have recently emerged as key checkpoints, limiting RIPK1 kinase activity and foiling TNF-mediated cytotoxicity. This, in turn, licenses the TNF-induced cytokine production that is necessary for a coordinated inflammatory response. Accurate checkpoint control is vital, given that many pathogens target NF-κB and mitogen-activated protein kinase (MAPK) signaling to evade detection; however, this removes critical survival checkpoints that can unleash the cytotoxic potential of RIPK1, thus killing infected cells and safeguarding host survival.